Effects of hematoma on the short-term fate of experimental microvenous autografts - (:unkn) unknown (THIEME MEDICAL PUBL INC, 1998)
The early effects of hematoma on the healing pattern of interpositional vein grafts were studied in 60 rats. In all animals, vein grafts approximately 10-mm in length were used to bridge defects created in the femoral artery and vein on the same side, with a 1:1 graft-to-host diameter match. Grafted vessels were completely covered with hematoma and separated from the surrounding tissue in 30 animals, while the other 30 rats served as controls. Both groups were divided into six subgroups of five animals each, according to the age of the grafts: 1, 3, 5, 7, 14, and 21 days. Graft patency and healing were assessed both clinically and histologically. 20/30 (66.6 percent) of the interarterial and 27/30 (90 percent) of the intervenous vein grafts in Group 1 (hematoma group), and 28/30 (93.3 percent) of the interarterial and 29/30 (96.6 percent) of the intervenous vein grafts in Group 2 (controls) were found patent. The patency rate of the interarterial vein grafts in the hematoma group was statistically significantly lower than in the control group and than in the intervenous vein grafts of the same group (p<0.005). The majority of interarterial vein-graft failures occurred after postoperative day 7 in Group 1. Patent specimens were examined under scanning electron and light microscopy. The authors concluded that perivascular hematoma caused spasm and flow disturbance, prolonged vessel-wall ischemia, and severe vessel-wall injury in the arterial circulation of the microvenous grafts. It also delayed the healing process and subjected the grafts to the development of occlusive mural thrombus. In contrast, the healing pattern of the intervenous vein grafts was not markedly influenced by perivascular hematoma, and equilibrium between thrombogenic and antithrombogenic factors on the graft surface was restored over a short period of time.
Keywords: AUTOGENOUS VEIN GRAFTS; THROMBUS FORMATION; MICROVASCULAR ANASTOMOSES; ARTERIAL SUBSTITUTES; INTIMAL HYPERPLASIA; SMALL VESSELS; RAT; MODEL; ENDOTHELIALIZATION; ENDOTHELIUM